Application of iron oxide nanoparticles in the diagnosis and treatment of leukemia - Wang, Yiling; Yang, Yan; Zheng, Xi; Shi, Jianyou; Zhong, Lei; Duan, Xingmei; Zhu, Yuxuan (Frontiers in Pharmacology, 2023)
Leukemia is a malignancy initiated by uncontrolled proliferation of hematopoietic stem cell from the B and T lineages, resulting in destruction of hematopoietic system. The conventional leukemia treatments induce severe toxic and a long series of unwanted side-effects which are caused by lack of specificity of anti-leukemic drugs. Recently, nanotechnology have shown tremendous application and clinical impact with respect to diagnosis and treatment of leukemia. According to considerable researches in the context of finding new nanotechnological platform, iron oxide nanoparticles have been gained increasing attention for the leukemia patients use. In this review, a short introduction of leukemia is described followed by the evaluation of the current approaches of iron oxide nanoparticles applied in the leukemia detection and treatment. The enormous advantages of iron oxide nanoparticles for leukemia have been discussed, which consist of the detection of MRI as efficient contrast agents, magnetic biosensors and targeted delivery of anti-leukemia drugs by coating different targeting moieties. In addition, this paper will briefly describe the application of iron oxide nanoparticles in the combined treatment of leukemia. Finally, the shortcomings of the current applications of iron-based nanoparticles in leukemia diagnosis and treatment will be discussed in particular.